2011
DOI: 10.1016/j.ecolmodel.2011.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Local calibration of coliforms parameters of water quality problem at Igapó I Lake, Londrina, Paraná, Brazil

Abstract: Summary. The calibration of a model refers to the process by which

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 24 publications
(2 reference statements)
0
17
0
6
Order By: Relevance
“…Regarding to the transport model parameters the following were taken: for the longitudinal and transversal diffusion coefficients ROMEIRO et al, 2011), and for deoxygenation coefficients values, 1 K in 1 d  , shown in Table 2. Regarding the boundary conditions, the BOD5 concentration at the T1 entry was taken as 12.6 mg / l, this value consistent with the experimental measurements.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding to the transport model parameters the following were taken: for the longitudinal and transversal diffusion coefficients ROMEIRO et al, 2011), and for deoxygenation coefficients values, 1 K in 1 d  , shown in Table 2. Regarding the boundary conditions, the BOD5 concentration at the T1 entry was taken as 12.6 mg / l, this value consistent with the experimental measurements.…”
Section: Resultsmentioning
confidence: 99%
“…In order to simulate the effects of such a discharge, a two-dimensional horizontal model, composed of a hydrodynamic model and a transport model, is used. In this model the water flow in the discretized geometry (CIRILO; BORTOLI, 2006) is described by Navier-Stokes and pressure equations in curvilinear coordinatethe hydrodynamic model - (ROMEIRO et al, 2011), whereas the transport of the concentration of biochemical oxygen demand, BOD 5 , is described by an advective-diffusive equation in curvilinear coordinatethe transport model - (PARDO et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This characteristic of this artificial lake explain the low rate of flow, which in turn presents, on average, a low Reynolds number. So, to calibrate the small pressure gradient from the boundary conditions, a low Reynolds number Re=10 was used (ROMEIRO et al, 2011).…”
Section: Numerical Simulationsmentioning
confidence: 99%
“…A OMS recomenda que as bactérias do grupo coliformes fecais sejam utilizadas como parâmetro microbiológico de qualidade d'água, quando se deseja mensurar a presença de organismos patogênicos [3]. Nos últimos anos um grande esforço tem sido realizado para desenvolver modelos matemáticos que descrevam adequadamente a dinâmica de coliformes fecais em diferentes corpos d'água [4,5,6]. Nesse contexto, estudar a dinâmica de coliformes fecais no corpo d'água do lago Luruaco é uma forma de determinar as regiões que apresentam maior risco de contaminação para a população local.…”
Section: Introductionunclassified
“…Neste contexto, utiliza-se as bactérias do tipo coliformes fecais (presentes principalmente no esgoto doméstico) como parâmetro para a qualidade da água. A dinâmica de concentração dos coliformes fecais é obtida por meio da simulação numérica de um modelo bidimensional horizontal (2DH) durante um determinado intervalo de tempo [6]. O modelo de transporte de coliformes fecais é dado por uma equação convectiva-dispersiva-reativa, cujo termo convectivo contém o campo de velocidades do fluxo hidrodinâmico, obtido a partir de um sistema de equações de Navier-Stokes.…”
Section: Introductionunclassified